Evaluation of the therapeutic relevance of architectural aspects in child and adolescent psychiatric institutions from the perspective of architects and senior physicians - Dustin Fornefeld; Fabian Schmoll-Klute; Daniel Halswick; Peter Schmidt; Marie-Léne Scheiderer; Lynn Reuter; Katharina Brockmann; Anna Pfersich; Oliver Fricke (BMC Psychiatry)
Abstract Objective The concept of “Healing Architecture” addresses the relevance of design and architectural issues on the outcome of medical and therapeutic treatment in hospitals. The questionnaire ARCHI was developed to record data on the opinion of different groups of users on the architectural design of their therapeutic environment in departments of child and adolescent psychiatry. Method A Questionnaire-based cross-sectional study was conducted in two phases between 2020 and 2022 using ARCHI to gather the perspectives of senior physicians and architects on the significance of architectural design in German child and adolescent psychiatric facilities. Results In the survey of the senior physicians, 49 heads of child and adolescents psychiatric departments initiated the survey, and 73.5% (n = 36) of them completed the questionnaire in its entirety. During the survey for the architect-specific, 145 individuals commenced the survey, and 60.7% of them completed the questionnaire (n = 88). Significant differences between architects and senior physicians became visible for four of the 93 items, namely “environment of the hospital”, “structure of building”, “labelling of floors” and “visible cleanliness”. Conclusions Although senior physicians and architects were characterized by the same opinions on the relevance of architectural design on therapeutic issues for the major part of issues, differences could be obtained for several aspects which are important for the architectural planning of new departments and hospitals. It remains open why both professional groups had different point of views on these four aspects of hospital design which should be clarified to improve the process of hospital development in the future.